Bimbingan Kelompok Dengan Teknik Self Control Dalam menumbuhkan Rasa Malu (Haya’) Remaja Di Desa Pedamaran - Lestarina, Wennii; Abdurrazzaq, Abdurrazzaq; Jannati, Zhila (CV. ITTC INDONESIA, 2022)
Group Guidance Using Self-Control Techniques in Growing Shyness (Haya') of Adolescents in Pedamaran Village This research aims to find out the effectiveness of i-group guidance with self-control techniques in growing a sense of shyness (haya') towards adolescents. This research uses a quantitative approach to the ion-group experiment. The sample technique used in this research used the random sampling technique in Iran, the data collection technique used the questionnaire (questionnaire), observation and documentation. iData analysis technique iusing iMicrosoft iExcel i2007, iSPSS iVersion i25 and iWilcoxon test. i. Data iteration test ivalidity i0.632 i and i stage test irreliability i0.932. The results of this study show that the level of shyness (feeling) has increased after being guided by the group with the self-control technique. If seen from i, the mean value of ipretest is i99 and it increases iafter ipostest is given, i get an average value i106 i, by using ione-group experiment approach. The results of this study show that i-group guidance with self-control techniques is effective in growing a sense of embarrassment (haya') i-teenagers in iPedamaran's ideas.